Implementation of the Uninhabitable House Repair Program (RUTILAHU) For Poor Families in Airlangga Village, Surabaya City - Santi Dewi Lestari; Dino Dwi Saputra; Tiara Aura Rizki (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Poverty and uninhabitable housing remain urgent issues in urban areas. The Uninhabitable Housing Rehabilitation Program (RUTILAHU) is a policy by the Surabaya City Government aimed at improving the housing quality of low-income communities, including those in Airlangga Subdistrict. This study analyzes the program’s implementation using George C. Edward III’s theory, which includes communication, resources, implementer disposition, and bureaucratic structure. A qualitative case study approach was used through interviews, observation, and documentation. The findings show that the program is relatively effective, although it faces challenges such as limited aid quotas, low technical capacity, and bureaucratic barriers. Implementers’ commitment and inter-agency coordination are key supporting factors. Strengthening human resources, increasing aid allocation, and simplifying procedures are necessary to make the program more optimal and well-targeted. Keywords: Poverty, Policy Implementation, Edward III, RUTILAHU, Airlangga Village.